2015 IEEE-RAS 15th International Conference on Humanoid Robots (Humanoids) 2015
DOI: 10.1109/humanoids.2015.7363448
|View full text |Cite
|
Sign up to set email alerts
|

Achieving "synergy" in cognitive behavior of humanoids via deep learning of dynamic visuo-motor-attentional coordination

Abstract: The current study examines how adequate coordination among different cognitive processes including visual recognition, attention switching, action preparation and generation can be developed via learning of robots by introducing a novel model, the Visuo-Motor Deep Dynamic Neural Network (VMDNN). The proposed model is built on coupling of a dynamic vision network, a motor generation network, and a higher level network allocated on top of these two. The simulation experiments using the iCub simulator were conduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…The VMDNN model was composed of 7 layers: the V I , V F , V S layers in the MSTNN subnetwork, the PFC layer, and the M S , M F , M O layers in the MTRNN subnetwork. The structure of the VMDNN model used in this study was found empirically in our preliminary experiments [46]. Note that the structure of the VMDNN model including the number of layers in each subnetwork can be extended depending on the complexity of the task since the 'deeper' structure can enhance learning of complex functions in visuomotor patterns [11].…”
Section: B Network Configurationmentioning
confidence: 99%
See 2 more Smart Citations
“…The VMDNN model was composed of 7 layers: the V I , V F , V S layers in the MSTNN subnetwork, the PFC layer, and the M S , M F , M O layers in the MTRNN subnetwork. The structure of the VMDNN model used in this study was found empirically in our preliminary experiments [46]. Note that the structure of the VMDNN model including the number of layers in each subnetwork can be extended depending on the complexity of the task since the 'deeper' structure can enhance learning of complex functions in visuomotor patterns [11].…”
Section: B Network Configurationmentioning
confidence: 99%
“…Each MSTNN layer consisted of a set of feature maps retaining the spatial information of the visual input. The for the time constant at each level of the model were found heuristically in our preliminary study [46].…”
Section: B Network Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed model consists of two pathways (visual and proprioceptive pathway for perceiving and predicting the dynamic visual images and the perceptual outcome of the robot's intended actions respectively) and those two pathways are tightly coupled by means of the lateral connection at the highest layers in each pathway and end-to-end training of the dynamic visuo-proprioceptive patterns. The proposed model is an extension of our previous model [1,7,8] which was able to abstract and associate visual perception with proprioceptive information through a spatio-temporal hierarchical structure. In the current study, we extended the previous model under the predictive coding framework [2][3][4][5] to endow the model with several key features.…”
Section: Introductionmentioning
confidence: 99%
“…Hwang et al [123] demonstrated gesture recognition with a recurrent model, and coordinated it with attention switching, object perception, and grasping. The robot focused on a human collaborator, who gestured to one of two objects.…”
Section: Examples In Recent Researchmentioning
confidence: 99%